Питание детей раннего и дошкольного возраста: пособие для воспитателя детского сада / В. Г. Кисляковская, Л. П. Васильева, Д. Б. Гурвич - Кисляковская Валентина Гавриловна (Просвещение, 1983)
Экземпляры: КХ (20190418) / Инвентарный номер: 804517 / Сис.шифр: 618Д / Авт.знак: К 44 / ГРНТИ: 76 / ББК: 5